Effectiveness of an educational intervention on the level of knowledge of COVID-19 in older adults - Yusnier Lázaro Díaz-Rodríguez; María de Los Ángeles Vargas-Fernández; Luis Amado Quintana-López (Universidad Médica Pinareña, 2020)
Introduction: the need for admission and mortality in older adults infected with COVID-19 is greater than in the general population, with knowledge about the disease determining risk perception and prevention.